2016
DOI: 10.3389/fcell.2016.00102
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Cardiac Side Population Cells in Cardiac Regeneration

Abstract: The heart has a limited ability to regenerate. It is important to identify therapeutic strategies that enhance cardiac regeneration in order to replace cardiomyocytes lost during the progression of heart failure. Cardiac progenitor cells are interesting targets for new regenerative therapies because they are self-renewing, multipotent cells located in the heart. Cardiac side population cells (cSPCs), the first cardiac progenitor cells identified in the adult heart, have the ability to differentiate into cardio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 60 publications
1
27
0
Order By: Relevance
“…Although it is unclear whether the heart can be made to regenerate, cardiac progenitor cells identified in the adult heart are multipotent and have the ability to differentiate (Beltrami et al . ; Yellamilli & van Berlo, ). A randomized control phase I clinical trial (SCIPIO) investigated whether isolating c‐kit + cardiac progenitor cell (CPCs) from patients and re‐introducing them back into the injured heart would be beneficial.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although it is unclear whether the heart can be made to regenerate, cardiac progenitor cells identified in the adult heart are multipotent and have the ability to differentiate (Beltrami et al . ; Yellamilli & van Berlo, ). A randomized control phase I clinical trial (SCIPIO) investigated whether isolating c‐kit + cardiac progenitor cell (CPCs) from patients and re‐introducing them back into the injured heart would be beneficial.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have identified follistatin like 1 (Masters & Riley, 2014;van Rooij, 2016), Pim-1 (Cottage et al 2010), growth differentiation factor 11 (Olson et al 2015;Rochette et al 2015;van Rooij, 2016) and insulin like growth factor 1 (Leifke et al 2000;Fontana et al 2012) as possible anti-ageing factors capable of inducing endogenous regeneration in the ageing heart. Although it is unclear whether the heart can be made to regenerate, cardiac progenitor cells identified in the adult heart are multipotent and have the ability to differentiate (Beltrami et al 2003;Yellamilli & van Berlo, 2016). A randomized control phase I clinical trial (SCIPIO) investigated whether isolating c-kit + cardiac progenitor cell (CPCs) from patients and re-introducing them back into the injured heart would be beneficial.…”
Section: Introductionmentioning
confidence: 99%
“…Coincidentally, it has been found that Akt1 dramatically enhances and expedites the formation of induced cardiac-like myocytes from fibroblasts in the presence of cardiac transcription factors GATA4, Mef2c, Hand2, and Tbx5 [61] . In addition, the cardiac side population, the first population of cardiac progenitor cells identified in the adult heart, can differentiate into cardiac lineages in response to cardiac injury, and thus could be a promising target for cardiac regenerative medicine [62] . The research concerning the usage of the regenerative ability of cardiomyocytes for heart regeneration has just started, but many exciting findings have been reported in just a few years.…”
Section: Resultsmentioning
confidence: 99%
“…SPCs were first described as a way to enrich for hematopoietic stem cells capable of long-term bone marrow reconstitution after transplantation into lethally irradiated mice (Goodell et al, 1996). Since then, SPCs have been identified in intestines, skeletal muscle, and the heart (Yellamilli & van Berlo, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Isolated cardiac side population cells (cSPCs) are enriched for cells that self-renew and differentiate into multiple cardiac lineages in cell culture and after transplantation. However, it is unknown whether the side population phenotype enriches for endogenous cardiac progenitor cells that can give rise to cardiomyocytes (Noseda et al, 2015;Oyama et al, 2007;Unno et al, 2012;Yellamilli & van Berlo, 2016). Cultured cSPCs form colonies at ten times the rate of other non-cardiomyocytes isolated from the heart (Martin et al, 2004;Pfister et al, 2005).…”
Section: Introductionmentioning
confidence: 99%